2020
DOI: 10.1128/jvi.01471-19
|View full text |Cite
|
Sign up to set email alerts
|

Labyrinthopeptins Exert Broad-Spectrum Antiviral Activity through Lipid-Binding-Mediated Virolysis

Abstract: To counteract the serious health threat posed by known and novel viral pathogens, drugs that target a variety of viruses through a common mechanism have attracted recent attention due to their potential in treating (re)emerging infections, for which direct-acting antivirals are not available. We found that labyrinthopeptins A1 and A2, the prototype congeners of carbacyclic lanthipeptides, inhibit the proliferation of diverse enveloped viruses, including dengue virus, Zika virus, West Nile virus, hepatitis C vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 64 publications
0
42
0
1
Order By: Relevance
“…Cell lines pretreated with different concentrations of the compounds before infection by CHIKV and ZIKV inhibit virus infection in the low micromolar-to-nanomolar range. A study of the peptide’s mechanism using 11 species of adsorbed lipids demonstrated that the virolysis effect occurred through the binding of labyrinthopeptins and lipid phosphatidylethanolamine to the viral membrane [ 254 ]. However, in vivo experiments of labyrinthopeptins are still needed.…”
Section: Interplay Of Virus Proteins and Host Factorsmentioning
confidence: 99%
“…Cell lines pretreated with different concentrations of the compounds before infection by CHIKV and ZIKV inhibit virus infection in the low micromolar-to-nanomolar range. A study of the peptide’s mechanism using 11 species of adsorbed lipids demonstrated that the virolysis effect occurred through the binding of labyrinthopeptins and lipid phosphatidylethanolamine to the viral membrane [ 254 ]. However, in vivo experiments of labyrinthopeptins are still needed.…”
Section: Interplay Of Virus Proteins and Host Factorsmentioning
confidence: 99%
“…209 Labyrinthopeptins A1 and A2, were found to inhibit the proliferation of many enveloped viruses including dengue virus, Zika virus, West Nile virus, hepatitis C virus, chikungunya virus, Kaposi's sarcoma-associated herpes virus, cytomegalovirus, and herpes simplex virus with mechanism of action showing that it induced virolytic effect through binding to the viral membrane lipid phosphatidylethanolamine (PE). 210 Several derivatives are currently available for treating different viral infections, 211 which makes it a promising compound for assessment against coronavirus and/or SARS-CoV-2 infection.…”
Section: Labyrinthopeptinmentioning
confidence: 99%
“…LabyA2 also showed antiviral activity against HSV, but was at least tenfold less potent than Laby A1 [ 43 ]. Recently, a study reported that Laby A1/A2 can inhibit the infection of cells by a series of enveloped viruses, including Dengue, Zika, West Nile, Hepatitis C, Chikungunya and Karposi’s Sarcoma-associated Herpes virus, with 50% inhibitory concentration (IC 50 ) in the low micromolar to nanomolar range, and it was clarified that Laby A1/A2 specifically interact with the envelope lipid PE (rather than sphingomyelin with an ethanolamine head group, phosphatidylcholine, or other eight lipid species tested), thereby disrupting the membrane to exert their antiviral effect [ 37 ]. Subsequently, the result of another mechanistic study supported the notion that an interaction between Laby A1/A2 and PE is critical for their antiviral activity, and verified that labyrinthopeptins exert virolytic effect on Respiratory syncytial virus (RSV) by disrupting virus particle membrane integrity [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that Laby A1/A2 have advantages over duramycin and cinnamycin in low cytotoxicity and lack of adverse drug effects. Thus, labyrinthopeptins are promising antivirals to be developed with efficacy against a broad range of viruses, and with favorable therapeutic index [ 37 , 44 ].…”
Section: Introductionmentioning
confidence: 99%